Territorial cohesion storylines in 2014–2020 Cohesion Policy. Issue 12 (2nd December 2017) - Nosek, Štěpán
ABSTRACT: The purpose of this paper is to elaborate the concept of territorial cohesion in the context of 2014–2020 Cohesion Policy. The main goal is to investigate how European Union (EU) Member States (MSs) are coping with territoriality in their policies and to assess whether they are only fulfilling the minimum standards of a place-based approach or whether they are moving towards a new paradigm of policy-making characterized by a more territorially sensitive approach. This paper analyses Partnership Agreements which were signed between the European Commission and EU MSs and identifies the perception of territorial cohesion in the Cohesion Policy in the programming period 2014–2020. The analysis shows that different MSs choose different ways of addressing territoriality of their policies. It is thus possible to categorize countries into several groups sharing similar features and to discuss underlying ideas and approaches, which could shed some light on the still rather fuzzy concept of territorial cohesion.